Reinterpretasi Makna Nafkah dalam Bingkai Islam Nusantara - Ahmad Rajafi (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2018)
The controversy about the concept of nafkah in Islam seems never ending, especially the strengthened of Islamic trans-national understanding in society which emphasizes the importance of Qur'an but with the scriptualistic model and denying other elements that can be formulated as a means to reinterpret verses of God, such as the verse of nafkah living that is used as a justification of men's power over the women. So that, examine the harmony of revelation and local culture in the context of the verse about nafkah with the approach of Islamic Nusantara is important to be explained in order to be create a responsive understanding and shalih li kulli zamân wa makân. The direction of that reinterpretation formulates the concept of economic agreement in a family, where the reading of the verse must be related to the early history of Islam which treats women in a minor but with positive progress toward the major treatment, so that women (wives) who were previously prohibited in earning of nafkah could be transformed to participate in constructing the economic family or even as the main provider of nafkah in a family.